Acaulospora aspera, a new fungal species in the Glomeromycetes from rhizosphere soils of the inka nut (Plukenetia volubilis L.) in Peru - Corazon Guivin, Mike Anderson (2019)
A new fungal species of the Glomeromycetes, Acaulospora aspera, was isolated from the rhizosphere of the inka nut (Plukenetia volubilis) in San Martín State of Peru (Western Amazonia) and propagated in bait cultures on Sorghum spp., Brachiaria brizantha, Medicago sativa and P. volubilis as host plants. The fungus forms brownish yellow to yellow brown spores, (120-)135-195 × (120-)130 187 μm in diameter. The surface of the structural spore wall layer is crowded with small depressions, 0.4-0.7 μm in diameter, up to 0.8 μm deep, and only 1.1-1.8 apart, giving the spore surface a rough, washboardlike appearance, especially when the outermost, evanescent wall layer has disappeared. Phylogenetically, the new species is close to A. spinosissima, A. excavata and to other morphologically more similar species such as A. spinosa and A. tuberculata, which form spiny or tuberculate projections on the outermost, semi-persistent spore wall layer, or A. herrerae, A. kentinensis, A. scrobiculata and A. minuta, which on the structural spore wall layer all have more pronunced pits than A. aspera. In this study, also the name of A. spinosissima was validated, as it had been preliminary declared invalid because of a typing error in the diagnosis section of its original description.